Anonymization - Weber, Rolf H. (SpringerBriefs in cybersecurity, 2012)
Within the last decade, the Internet has developed as a phenomenon encompassing social, cultural, economic and legal facets. It has become common practice to use the Internet for both the retrieval and provision of information, with the result that the Internet has become a valuable tool in everyday life. Many Internet participants are unaware that they leave data tracks on every website they pass; surfing on the World Wide Web is far from being an anonymous activity of no consequence. In recent years a number of networking techniques have been initiated in order to accommodate the netizen's wish for anonymous communication and the protection of their privacy in the online world. Anonymization explores the legal framework developed to help protect netizens' privacy and their wish for anonymous communication over the Internet. It debates the value in helping to protect anonymity over a network which sees an increasing number of cybercrimes, and explores governmental interventions into anonymity requests, and whether requests should only be legal if a sufficiently legitimized public interest is given.